Suppression of hydrogen evolution at catalytic surfaces in aqueous lithium ion batteries. Issue 30 (24th July 2020) - Wang, Fei; Lin, Chuan-Fu; Ji, Xiao; Rubloff, Gary W.; Wang, Chunsheng
Abstract : We investigated the catalytic activity of different coating layers and put forward a selection criterion for surface layers. Al2 O3 could effectively suppress HER and enable the cycling of Li4 Ti5 O12 anode in water-in-salt electrolyte, with a capacity of 145 mA h g −1 . Abstract : Aqueous lithium ion batteries (ALIBs) have attracted increasing attention due to their excellent safety profile. The water-in-salt electrolyte (WiSE) has enabled a wider voltage window (3.0 V) through the formation of an solid–electrolyte–interphase (SEI) on the anode. However, the cathodic limit of the WiSE and its derivatives cannot effectively support the desired energy-dense anodes, such as Li4 Ti5 O12 (LTO). At the anode, the hydrogen evolution reaction (HER) is the main parasitic process that competes with the desired lithiation process therein. We investigated the catalytic activity of different coating layers and postulated the selection criterion for the surface layers. We demonstrated that Al2 O3 had a surface that effectively suppressed the HER and enabled the cycling of the LTO anode in the WiSE, thereby delivering a capacity of 145 mA h g −1 . Such understanding provides important guidelines for designing electrolytes and interphases for aqueous battery chemistries.